School-based Indigenous cultural programs and their impact on Australian Indigenous students: a systematic review. Issue 1 (1st January 2021) - Lowe, Kevin; Tennent, Christine; Moodie, Nikki; Guenther, John; Burgess, Cathie
ABSTRACT: This critical systematic review of Australian research literature provides insights into the aspirations of Indigenous communities to collaborate with schools in establishing local Indigenous language and cultural programmes. This systematic review investigates the body of Australian research into the cultural, social and educational impacts on those Aboriginal and/or Torres Strait Islander students who have had opportunities to engage with these school-based Indigenous languages and/or cultural programmes. The review found that while many Indigenous families have advocated for their children's to have access to quality language and cultural programmes, barriers of indifference, resourcing and leadership, have worked to limit students' ability to access to these programmes. The studies highlight the effects on students sense of identity, the strengthening connectedness to community and County and the intergenerational sharing of cultural knowledge.